Locus TUTOU2 determines the panicle apical abortion phenotype of rice (Oryza sativa L.) in tutou2 mutant - Zi-chao ZHU; Sheng LUO; Bin LEI; Xian-yong LI; Zhi-jun CHENG (Journal of Integrative Agriculture, 2022)
Rice panicle apical abortion (PAA) is a detrimental agronomic trait resulting in spikelet number reduction and yield loss. To understand its underlying molecular mechanism, we identified one recessive PAA mutant tutou2 from the offspring of tissue cultures. The mutation locus was finely mapped to a 75-kb interval on the long arm of chromosome 10. Sequence analysis revealed a single nucleotide substitution of A to T at the 941 position of LOC_Os10g31910 in tutou2, resulting in an amino acid change from isoleucine to phenylalanine. Complementation analysis showed that the degenerated panicle phenotype in tutou2 was rescued in the transgenic lines. A phenotype similar to tutou2 can also be obtained by LOC_Os10g31910 knockout in wild-type rice. These results suggested that LOC_Os10g31910 is the causative locus TUTOU2 responsible for the tutou2 PAA phenotype and probably also the locus of DEL1, previously documented as a leaf senescence gene. The significant phenotypic differences between del1 and tutou2 suggest that the locus DEL1/TUTOU2 plays roles in both leaf and panicle development which were not considered fully in previous studies.